Pre-Planning in Piedmont Areas: the Strategic Plan “Pinerolese Yard: Towards a Plain-Mountain Network” of the Pinerolese Homogeneous Zone (Piedmont, Italy) - Maria Anna Bertolino (Revue de Géographie Alpine)
This paper is about city-mountain relationship as pointed out in a pre-planning work done by the Pinerolese Homogeneous Zone of the Metropolitan City of Turin (Western Italian Alps) and supported by the “Call for technical assistance for the elaboration of local territorial development strategies” of the program “Turin and the Alps” from the Compagnia di San Paolo Foundation (Turin). The pre-planning work led to a strategic plan called “Pinerolese yard: toward a plain-mountain network”. During its planning, the city of Pinerolo established a dialogue with the different local mountain actors that marked a new vision for the entire territory. This vision called for the overcoming of the core-periphery model, which emerged in the area in the last century because of economic and social dynamics such as depopulation and desertification of the traditional mountains activities. Moreover, both the administrative reconstruction of the Metropolitan City of Turin and the macro-regional strategy Eusalp are nowadays external forces that require a joint public action between urban and mountain territories in order to reach a greater territorial competitiveness, especially in medium-sized territories, such as the Pinerolese Homogeneous Zone. This could be achieved in different ways: on the one hand by structuring an alternative offer to the metropolis in terms of goods and services, on the other by better managing the city-mountain interchange.